On some properties of the Diophantine equations a2 = b2 ± bc +c2 - Majumdar, Abdullah Al Kafi (Journal of Bangladesh Academy of Sciences, 2021)
This paper gives some properties related to the Diophantine equations a2 = b2 ± bc +c2. It has been shown that, in some cases, each of the two Diophantine equations has multiple solutions. The formulas for multiple solutions are derived. J. Bangladesh Acad. Sci. 45(1); 123-125: June 2021